2012
DOI: 10.1007/s10853-012-6361-y
|View full text |Cite
|
Sign up to set email alerts
|

Survey of structural and electronic properties of C60 on close-packed metal surfaces

Abstract: The adsorption of buckminsterfullerene (C 60 ) on metal surfaces has been investigated extensively for its unique geometric and electronic properties. The twodimensional systems formed on surfaces allow studying in detail the interplay between bonding and electronic structures. Recent studies reveal that C 60 adsorption induces reconstruction of even the less-reactive close-packed metal surfaces. First-principles computations enable access to this important issue by providing not only detailed atomic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 82 publications
4
44
0
Order By: Relevance
“…For an isolated C 60 , it is known that the electron charge density is higher on 6:6 CÀC bonds connecting hexagonal facets than on 6:5 CÀC bonds connecting pentagonal and hexagonal facets. 28 The C atoms involved in the bonding appear to be those involved in 6:6 bonds at DS sites and in 6:5 bonds at WF sites. This suggests that the bonding is more favorable between electron-poor Al substrate ARTICLE atoms and electron-rich 6:6 bonds at DS sites as well as between the electron-rich Mn atom and the electron-deficient 6:5 bonds at WF sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For an isolated C 60 , it is known that the electron charge density is higher on 6:6 CÀC bonds connecting hexagonal facets than on 6:5 CÀC bonds connecting pentagonal and hexagonal facets. 28 The C atoms involved in the bonding appear to be those involved in 6:6 bonds at DS sites and in 6:5 bonds at WF sites. This suggests that the bonding is more favorable between electron-poor Al substrate ARTICLE atoms and electron-rich 6:6 bonds at DS sites as well as between the electron-rich Mn atom and the electron-deficient 6:5 bonds at WF sites.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed C 60 adsorption on normal crystalline surfaces allows symmetry matching only with either 2-fold or 3-fold symmetry axis, corresponding to adsorption geometries where the molecule lies either on a 6:6 CÀC bond or on a hexagonal face. 28 On QC substrates, one expects most of the C 60 to be adsorbed on a pentagonal C face, and this should influence the properties of the molecular film in a unique way. These results could be expanded by functionalizing the molecules to investigate the physical properties of model 2D quasiperiodic systems, for example to study magnetic frustration on a quasiperiodic lattice by using endohedral fullerenes with magnetic moments.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, we have identified the two lowest energy configurations which will be referred to as dimer30 and hex0. They correspond to (i) the molecule sitting on a 6 : 6 dimer bridging between two Pt-hexagons at 30°with respect to the [1][2][3][4][5][6][7][8][9][10] surface direction for dimer30, and to (ii) the fullerene oriented on a carbon hexagon on top of a Pt hexagon on the surface for hex0 (see figure 6). These two configurations have been recalculated with VASP and they provide the basis for the rest of our theoretical study.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…C 60 usually forms large-unit-cell self-assembled monolayers when deposited on metal surfaces [3]. There is an extended bibliography on thin films of C 60 on many different single crystal metal substrates as Pt [4][5][6][7][8][9][10], Al [11,12], Cu [13][14][15][16][17][18], Au [19][20][21][22][23][24][25][26][27][28] and Ag [29][30][31][32][33][34] or even on graphene [35], among many others.…”
Section: Introductionmentioning
confidence: 99%
“…C 60 adsorption has been studied on several metal surfaces, 1 including Ag(111), 2 Al(111), 3 and Pt(111): 4,5 these metals were found to reconstruct into a one-metal-atom vacancy structure, in which one metal atom is missing under each C 60 molecule. A study of C 60 on Cu(111) performed by Pai et al 6 found that after deposition of C 60 and annealing to 500 K, the C 60 molecules sink into the Cu(111) surface by ∼2Å, which is close to the Cu(111) interlayer spacing.…”
Section: Introductionmentioning
confidence: 99%